In Vitro Comparison of the Effectiveness of Chlorhexidine and Two Calcium Hydroxide Formulations on Enterococcus Faecalis - Sharifian, Mohammad Reza; Shokouhinejad, Noushin; Aligholi, Marzieh Aligholi; Emaneini, Mohammad; Katebi, Arash; Assadian, Hadi (Iranian Endodontic Journal, 2009)
INTRODUCTION: The aim of this in vitro study was to compare the effectiveness of three intracanal medicaments in disinfecting the root canal and dentin of experimentally infected human teeth with Enterococcus faecalis (EF). MATERIALS AND METHODS: One hundred extracted human single-rooted teeth were used. After root canal preparation, teeth were mounted in epoxy resin. Following sterilization, the teeth were infected for 28 days with EF. Then root canals were filled with one of three different disinfectants: viscous 2% Chlorhexidine (CHX), calcium hydroxide paste (CH) or a mixture of CH and CHX (n=30 in each group). Antimicrobial assessments were performed at 1, 3 and 7 days (n=10 in each time period). Microbial samples were obtained from root canals before and after the experiment. Also dentin samples were examined. The data was analyzed using Two- Way ANOVA test. RESULTS: The findings showed that there was no difference between experimental groups at different time periods. The mixture of CH/CHX in 7 days was able to eliminate EF completely from root canal system. The most elimination of EF was from dentinal tubules. CONCLUSION: According to the results of this in vitro study, viscous 2% CHX, mixture of CH with distilled water and 2% CHX are all effective disinfectants.